From Tradition to Trend: Development, Acceptability and Marketability of Classic Heirloom Rice-Veggie Chips - Uy-uyon, Drinarie B.; Pinyuhan, Chabelita D.; Mad-ang, Regina A.; Buyaco, Alayne Kaye D.; Abello, Divine Grace P.; Malinao, Client William M. (Future Science / FSH-PH Publications, 2025)
Heirloom rice is part of the culture and heritage of the Cordillera Ad-ministrative Region. It is the heart and soul of its terraces. Heirloom rice varieties are now known to be nutrient-dense, thus elevating heirloom rice’s status as a specialty rice. The production of processed products from heirloom rice lacks standardization of the processing procedures as most of the processed products are done by small-scale entrepreneurs in the locality. Thus, this study aims to develop a new variety of chips out of heirloom rice of Ifugao, fused with additional vegetables like Moringa Oliefera (Horse Radish Leaves) and Ma-mordica Charantia (Bitter Gourd Leaves). The developmental re-search design was used to develop the Classic Heirloom Rice-Veggie Chips. In contrast, the quantitative-descriptive research design among 315 randomly selected consumers in Lagawe, Ifugao, was used to determine the acceptability and marketability aspect of the product developed. After a series of formulations, the study devel-oped a standardized process and procedures for making Heirloom Rice- Veggie Chips. On the other hand, using weighted means, findings revealed that the product received high acceptability ratings across all attributes, with texture scoring 5.86 and overall acceptability reaching 5.92, indicating strong positive appeal to respondents. Thus, heirloom rice with vegetables is generally acceptable for sensory evaluation. Lastly, The Classic Heirloom Rice Veggie Chips demon-strated high marketability across various aspects, with strong scores in purchase likelihood (5.79), recommendation (5.93), recognition (5.94), and packaging (5.98) while maintaining consistent appeal across different price points.